From student to teacher: finding mindful ways to grow in the face of stress - Draper-Clarke, Lucy J (My University, 2014)
The severity of stress in the teaching profession is a worldwide phenomenon, and recent concern has focused on the number of student teachers who leave soon after qualifying. The benefits of mindfulness practices have been firmly established in the medical arena, particularly for stress-related illnesses. Studies are now being conducted within education, and research is investigating the potential of mindfulness for personal and professional growth. This interdisciplinary study focuses on student teachers, and by taking a developmental approach, explores whether mindfulness provides a catalyst for the effective transition from student to teacher. The outcomes of a mindfulness-based intervention (MBI) were examined with a sample of South African student teachers at the Witwatersrand School of Education (n=14). Participants attended a series of interviews over a five-month period, attended a sixweek MBI, and completed self report questionnaires on depression, anxiety and stress, facets of mindfulness, and self-compassion. Results from the mixed-methods study revealed that common causes of stress were seriously exacerbated by the Gauteng context. Most student teachers were experiencing depression, anxiety and stress of clinical levels, yet with the provision of little clinical support. The students who participated in the MBI revealed a range of pre-existing coping strategies, and added mindfulness practices to their repertoire at differing levels of effectiveness. A Developmental Model of Mindfulness was developed as a result of the research process, in order to advise on the different types of practice, and different expectations of results, at each developmental stage. The proposed categories are restorative, dynamic and transformative mindfulness. Qualitative data from interviews were explored to identify themes, showing dialectical shifts as tensions were identified and new behaviours explored. Further research is needed to explore long-term dispositional development beneficial for a teaching career, but initial findings provide subjective evidence from students that mindfulness may be a valuable mediator of change within the context of teacher education.
A thesis submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg 19th June 2014